223k views
4 votes
Solve the equation
-2(n + 1) = 6
(PLEASE HELP)

Solve the equation -2(n + 1) = 6 (PLEASE HELP)-example-1
User Seldaek
by
5.0k points

2 Answers

4 votes

Answer:

n=-4

Explanation:

1. Write the equation.

-2(n+1)=6

Simplify.

= -2n-2=6

2. Add 2 to both of the sides to make it equal.

= -2n-2=6

+2 +2

= -2n=8

3. Divide by -2 on both sides.

= -2n/-2=8/-2

= n=-4

User Bibliophilsagar
by
5.3k points
0 votes

Answer:

n= -4

Explanation:

Distribute the -2 on the left sides

-2(n+1)=6

-2*n + -2*1=6

-2n-2=6

Add 2 on both sides

-2n=8

Divide by -2 on both sides

n= -4

Hope this helps! :)